OLFM4 Regulates Lung Epithelial Cell Function in Sepsis-Associated ARDS/ALI via LDHA-Mediated NF-κB Signaling - Gong F; Li R; Zheng X; Chen W; Zheng Y; Yang Z; Chen Y; Qu H; Mao E; Chen E (Dove Medical Press, 2021)
Fangchen Gong,1,* Ranran Li,2,* Xiangtao Zheng,1,* Weiwei Chen,1 Yanjun Zheng,1 Zhitao Yang,1 Ying Chen,1 Hongping Qu,2 Enqiang Mao,1 Erzhen Chen1 1Department of Emergency, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China; 2Department of Critical Care Medicine, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Erzhen Chen; Ying ChenDepartment of Emergency, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, Ruijin 2# Road No. 197, Shanghai, 200025, People's Republic of ChinaTel +862164370045Fax +862164333548Email rjchenerzhen@163.com; bichatlion@163.comBackground: Acute respiratory distress syndrome (ARDS) is one of the leading causes of death in patients with sepsis. As such, early and accurate identification of sepsis-related ARDS is critical.Methods: Bioinformatic analysis was used to explore the GEO datasets. ELISA method was used to detect the plasma or cellular supernatant of relevant proteins. Quantitative real-time PCR was used for mRNA measurements and Western blot was applied for protein measurements. Immunohistochemistry staining and Immunofluorescence staining were used to identify the localization of OLFM4. Cecal ligation and puncture (CLP) model was used to establish sepsis model.Results: The bioinformatic analysis results identified ten genes (CAMP, LTF, RETN, LCN2, ELANE, PGLYRP1, BPI, DEFA4, MPO, and OLFM4) as critical in sepsis and sepsis-related ARDS. OLFM4, LCN2, and BPI were further demonstrated to have diagnostic values in sepsis-related ARDS. Plasma expression of OLFM4 and LCN2 was also upregulated in sepsis-related ARDS patients compared to septic patients alone. OLFM4 expression was significantly increased in the lung tissues of septic mice and was co-localized with Ly6G+ neutrophils, F4/80+ macrophages and pro-surfactant C+ lung epithelial cells. In vitro data showed that OLFM4 expression in lung epithelial cells was downregulated upon LPS stimulation, whereas neutrophil media induced OLFM4 expression in lung epithelial cells. Overexpression of OLFM4 and treatment with recombinant OLFM4 effectively suppressed LPS-induced pro-inflammatory responses in lung epithelial cells. Furthermore, the increased levels of LDHA phosphorylation and the downstream NF-κB activation induced by LPS in epithelial cells were effectively diminished by OLFM4 overexpression and recombinant OLFM4 treatment via a reduction in ROS production and HIF1α expression.Conclusion: OLFM4 may regulate the pro-inflammatory response of lung epithelial cells in sepsis-related ARDS by modulating metabolic disorders; this result could provide new insights into the treatment of sepsis-induced ARDS.Keywords: sepsis, ALI/ARDS, lung epithelial cells, inflammation, OLFM4, LDHA